Pentingnya Ukuran Kinerja Nonfinansial dalam Balanced Scorecard, Komitmen Organisasi, dan Kinerja Manajerial - Praja Hadi Saputra; Hamid Bone; Linayati Lestari (Journal of Applied Accounting and Taxation, 2020)
This study investigates the role of the degree of importance of using nonfinancial performance measures (in Balanced Scorecard) by superiors for performance evaluation in influencing employee performance through organizational commitment. This study adopted a quantitative research design and conducted a cross-sectional survey by questionnaire to collect responses from 118 local managers in Samarinda, Indonesia. Based on PLS analysis, the results of this study indicate that the use of nonfinancial measures in Balanced Scorecard for performance evaluation is significantly affect employee organizational commitment and directly affect managerial performance through organizational commitment. The results also prove that organizational commitment has a mediation role in the relationship between nonfinancial measures and performance. This study provides valuable insight that the degree of importance of the use of nonfinancial measures by superiors to evaluate performance can improve employee commitment and performance. Practically, the results provide an overview for superiors to be more comprehensive in developing a performance measurement system because the system has a crucial role in influencing employee behavior.